2001
DOI: 10.1067/mtc.2001.117838
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative use of tirofiban hydrochloride (Aggrastat) does not increase surgical bleeding after emergency or urgent coronary artery bypass grafting

Abstract: Patients may safely undergo coronary artery bypass surgery after treatment with tirofiban hydrochloride. This molecule, administered in the immediate preoperative period, has no adverse clinical effects and does not seem to negatively influence the incidence of perioperative myocardial infarction. Although extracorporeal circulation can modify platelet numbers and function, our ongoing data could show significant reduction in the loss of platelets induced by cardiopulmonary bypass, minor postoperative bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 13 publications
(9 reference statements)
2
46
0
1
Order By: Relevance
“…The few studies that did, have not noted excessive post-operative bleeding after treatment with tirofiban [14]. In most studies however, patients with emergency CABG and prior use of tirofiban showed no enhanced or even reduced bleeding rates [15].…”
Section: Bleeding Complications-the Evidencementioning
confidence: 97%
“…The few studies that did, have not noted excessive post-operative bleeding after treatment with tirofiban [14]. In most studies however, patients with emergency CABG and prior use of tirofiban showed no enhanced or even reduced bleeding rates [15].…”
Section: Bleeding Complications-the Evidencementioning
confidence: 97%
“…26 Also, biochemical markers show less activation of the hemostatic and inflammatory system. 61 However, despite these initial promising reports about the effects of GPIIb/IIIa blockers during cardiac surgery, 26,62,63 the currently available agents, particularly abciximab, are too long-acting to provide controllable platelet inhibition that is restricted to the time period of the actual surgical intervention and thus are feared to result in bleeding complications after the surgical procedure. 59,60,64 -67 Overall, because of the dichotomy of antithrombotic (antiischemic) and antihemostatic effects of the currently clinically available antiplatelet drugs, strong evidence for the overall benefit of platelet inhibition in CABG has not been demonstrated.…”
Section: Topcic Et Almentioning
confidence: 99%
“…In respect to protein IIb/ IIIa inhibitors, the surgeries were scheduled for 12 hours after drug cessation, which could have influenced our results. BIZZAARRI et al [23] did not identify differences in the postoperative bleeding in patients who had taken tirofiban as little as two hours before emergency surgery. Unfractioned or low molecular weight heparin, at any time in the preoperative period, did not influence the bleeding.…”
Section: Commentsmentioning
confidence: 99%